Cabaran Tamadun Islam dalam Era Pembaratan: Satu Sorotan - Yusof, Abdullah (Jurnal Usuluddin, 1998)
The Muslim world is currently plagued with almost nothing but negative attributes of a civilization. It must be regrettably acknowledged that Western Civilization's short-comings and weaknesses are no fewer than its advantages. The Muslim countries are undoubtedly associated with underdevelopment, backwardness, poverty, inequitable income and wealth distribution, high inflation, accute illiteracy and serious unemployment, economic and political instability, etc. Islam wants its followers to be self sufficient, independent and progressive as a resut of Islamic Practice. Therefore, this article will focus on some major challenges related to Islamic Civilization in Westernizational Era.